General Knowledge & Attitude of First Aid among Schoolteacher’s in Palestine - Mohammad Qtait, Nawaf Rn Amro (International Journal of Innovative Research in Medical Science, 2017)
First aid is the initial assistance or treatment given at the site of accident to someone who is injured or suddenly taken ill, before the arrival of ambulance. However, first aid provider should be able to assess the situation quickly and calmly, deal with life threatening conditions meanwhile protecting him/her self from the danger, obtain medical aid and call an ambulance in case of serious injury or illness. A cross-sectional study was carried out among schoolteacher's in southern of Hebron, simple random sampling was used to selected the schools and 150 schoolteacher's was selected from 8 schools by using convenience (purposive) sampling. A self-administered survey was distributed to a proportionate sample of 150 schoolteacher's designed from several studies to achieve the goal of this study. The total mean score knowledge of general first aid is 71.41%. Most of teachers answered correct of important balanced diet and the suitable management for hypoglycemic for diabetic patients (87.3%) and (77.3%) respectively.